2019
DOI: 10.1182/blood-2018-10-881722
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF inhibition reduces cytokine release syndrome and neuroinflammation but enhances CAR-T cell function in xenografts

Abstract: Chimeric antigen receptor T (CAR-T) cell therapy is a new pillar in cancer therapeutics; however, its application is limited by the associated toxicities. These include cytokine release syndrome (CRS) and neurotoxicity. Although the IL-6R antagonist tocilizumab is approved for treatment of CRS, there is no approved treatment of neurotoxicity associated with CD19-targeted CAR-T (CART19) cell therapy. Recent data suggest that monocytes and macrophages contribute to the development of CRS and neurotoxicity after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
434
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 483 publications
(460 citation statements)
references
References 32 publications
5
434
0
2
Order By: Relevance
“…10,[30][31][32] These cytokines have also been implicated in a number of other CNS diseases 33 and are known to activate the endothelial cells at the BBB, 9,34,35 supporting the theory that ICANS is initiated by a systemic cytokine surge. Key inflammatory cytokines showed similar elevations in the CSF and serum, suggesting that local cytokine production in the CNS is not a prominent feature of neurotoxicity.…”
Section: Discussionmentioning
confidence: 82%
“…10,[30][31][32] These cytokines have also been implicated in a number of other CNS diseases 33 and are known to activate the endothelial cells at the BBB, 9,34,35 supporting the theory that ICANS is initiated by a systemic cytokine surge. Key inflammatory cytokines showed similar elevations in the CSF and serum, suggesting that local cytokine production in the CNS is not a prominent feature of neurotoxicity.…”
Section: Discussionmentioning
confidence: 82%
“…Our group has previously described monocyte/macrophage derived cytokine enrichment in blood and cerebrospinal fluid, including G-CSF and GM-CSF, with neurologic toxicity in ALL patients treated with 19-28z CAR-T. 45 A recent report from the Mayo Clinic demonstrated that, in a xenograft model, neutralization with an anti-GM-CSF can abrogate neuroinflammation. 46 We sought to immunophenotype the end of production 19-28z CAR T cells to establish correlations with outcomes. Somewhat surprisingly, higher percentages of naïve-like CD45RA+CCR7+ T cells within both CD4 and CD8 subsets of the CAR T products correlated with greater likelihood of progression events.…”
Section: Discussionmentioning
confidence: 99%
“…These data are further supported by the evidence that human pulmonary microvascular endothelial cells (HPMEC) are able to secrete GM-CSF following an inflammatory stimulus such as LPS, suggesting a potential important role in the pathogenesis of ARDS, in which increased levels of GM-CSF are present in BAL fluid [301]. Additionally, animal models have demonstrated that GM-CSF neutralization is effective in reducing the severity of neuroinflammation induced by CAR-T therapy, with no negative effect on its efficacy [302].…”
Section: Granulocyte-monocyte Colony Stimulating Factormentioning
confidence: 93%